Deskripsi Hasil Belajar Matematika Siswa di SMP Muhammadiyah Tolangohula - Kue, Hawai Abas; Badu, Syamsu Qamar; Resmawan, Resmawan; Zakiyah, Siti (Research in the Mathematical and Natural Sciences, 2022)
This study aims to describe students' mathematics learning outcomes in the even semesters of the 2019/2020 school year. This research was conducted at SMP Muhammadiyah 1 Tolangohula using a descriptive method involving 19 students as research samples. The data obtained from the mathematics learning outcomes of class VII students who took the even semester exam where the test was presented in the form of objective questions and essays involving several indicators: (1) knowledge, (2) understanding, (3) application and (4) analysis. Then described in the form of mean  , median (Me), mode (Mo), histogram and percentage. The results showed that students' mathematics learning outcomes in even semesters were in a very low category with the percentage in the very low category as much as 84.21%, as much as 0% in the low category, as much as 10.53% in the medium category, as much as 0% in the high category. and there are as many as 5.26% in the very high category.